(3eZfi GddHjH Yf cJH GdCYGQjHs - (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, J (B761 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg Ydi CaVGdg aEf Chdi eG JbJQMg GdbQGY hYdi eG JLfM Edi JMUjdg GdLhGfM eG JjSQ Hg age cJGH Gddg GdefRd s
(3BNQgG (B:s
(3hdh PcQJ CMQa GdLQ hMhd HYVgG Ydi HYV ai eYfGg dLGA ef Pdc CeKdI cKjQI hgPG BNQ eG JjSQ GjQGOg ai gPG GdJCdja fLR HMeO Gddg hYhfg s
(3dYdgG fSNI GdCUd Ch GdfSN Hbde GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1751s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1767) s
Keywords: (3GdfMhs